If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3y = 12 + -2x Solving -3y = 12 + -2x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Divide each side by '-3'. y = -4 + 0.6666666667x Simplifying y = -4 + 0.6666666667x
| 3(2z-25)-2(z-1)=78 | | 20=4x+3x | | -6(n+1)-2(1-8n)=n-7+8 | | 6+4m=5(m+1) | | 3y+2x=2(y-2x) | | 6(x+9)=8x+8-2x+46 | | 63(5x+4/9)=6(50x-1/3) | | 10+3n=14 | | 6x-9=6(x+9) | | 0.5(x+100)=0.58x-574 | | -16t^2+24t=0 | | 6x-4y=7 | | N/-2=8 | | -4=-10/86+8 | | (7x^3*(2x^2)^2)/(10x^5) | | 3.4x=2.6x+5.6 | | (x/9)=(x/10)-8 | | x/9=x/10-8 | | 100(2+x)=100 | | (x-1)3+64=0 | | f(x)=-2x^2+5x+40 | | 10(z+2)-2(z-2)=3(z-3)+4(z-1) | | 0.4(0.7-4x)=-1.1x | | 459x+1377-23=8x+160 | | R/-6=-4 | | x^6/5-729=0 | | 50=-2(23-y)+4(y-3) | | v^2+15v+56= | | 2(x+1)(x-1)-(2x+3)(x-2)=0 | | 12m=56+12m | | x^3-4x^2-x-10=0 | | 14x^2=16 |